Analysis of samples from finite population - Turkuvienė, Jurgita; Bikelis, Algimantas (Lietuvos matematikos rinkinys, 2008)
This paper deals with asymptotic properties of probabilitydistributionsof sample statistics when samples are selected from finite populations.These properties also were analysed by P. Erdos, A. Rényi [3] and J. Hájek [4]. Relationships between probability distributions of sample sums were investigated in [6] article.
Keywords: finite population; Appel polynomial; Bernoulli sampling